Upaya Relasional dan Outcome Relasional dalam Membangun Retensi Pelanggan pada Peritel - Utami, Christina Whidya (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2006)
This research tries to elaborate how the relationship trough relationship outcomes in hypermarket and warehouse store can influence the customer retention. The research sample was shoppers in hypermarket and warehouse store in Surabaya which run relationship efforts' such as Carrefour, Makro, Alfa, Indogrosir and Hypermart. :,